A Decade of Digital Da'wah: Global Research Trends And Thematic Evolution (2013 - 2025) - Choirin, Muhammad; Abdul Kadir, Fakhrul Adabi; Setiyanti, Anis; Larhzizer, Fouad; Iqbal, Moch. (el Harakah: Jurnal Budaya Islam, 2025)
Over the past decade, the proliferation of digital platforms has significantly transformed the landscape of Islamic preaching, giving rise to what is now widely referred to as Digital Da’wah. Despite existing studies on content and communication strategies, few have systematically mapped the global scholarly trends in Digital Da’wah. This study addresses that gap through a comprehensive bibliometric review. It presents a comprehensive bibliometric analysis of global scholarly output on Digital Da’wah between 2013 and 2025, aiming to identify research trends, influential authors, collaborative networks, and thematic evolution within the field. Utilizing data from the Scopus database, the analysis employs tools such as Biblioshiny and the R programme to generate visual mappings of keyword co-occurrence, citation patterns, and thematic clusters. To interpret thematic shifts, this study employs frameworks from Islamic communication theory and digital sociology, offering insights into how da’wah adapts to digital contexts. The results reveal a steady increase in scholarly attention toward topics such as social media da’wah, digital Islamic communication, online religious authority, and youth engagement in Islamic content. Additionally, the study uncovers the geographical distribution of publications, with significant contributions from Southeast Asia, the Middle East, and Western academia. Thematic evolution analysis indicates a shift from early focus on content production and media ethics to recent concerns about algorithmic visibility, digital literacy, and da’wah effectiveness in virtual spaces. This research contributes to a deeper understanding of how Digital Da’wah has evolved as an academic field and offers insights for scholars, practitioners, and policymakers involved in Islamic communication and media studies. Dalam satu dekade terakhir, perubahan platform digital telah secara signifikan mengubah lanskap da'wah Islam, yang kini dikenal luas sebagai da'wah Digital. Meskipun sejumlah studi telah membahas konten dan strategi komunikasi dalam da'wah digital, kajian yang secara sistematis memetakan tren keilmuan global dalam bidang ini masih terbatas. Studi ini mengisi kekosongan tersebut melalui tinjauan bibliometrik yang komprehensif. Penelitian ini menganalisis output keilmuan global tentang da'wah Digital pada rentang waktu 2013 hingga 2025, dengan tujuan mengidentifikasi tren penelitian, penulis berpengaruh, jaringan kolaboratif, serta evolusi tematik dalam bidang ini. Data diambil dari basis data Scopus, dan dianalisis menggunakan alat seperti Biblioshiny dan program R untuk menghasilkan pemetaan visual keterkaitan kata kunci, pola sitasi, dan klaster tematik. Untuk menafsirkan pergeseran tematik, studi ini menggunakan kerangka teori komunikasi Islam dan sosiologi digital, guna memahami bagaimana da'wah beradaptasi dalam konteks digital. Hasil penelitian menunjukkan peningkatan perhatian akademik terhadap topik seperti da'wah melalui media sosial, komunikasi Islam digital, otoritas keagamaan daring, dan keterlibatan pemuda dalam konten keislaman. Studi ini juga mengungkap distribusi geografis publikasi, dengan kontribusi signifikan dari Asia Tenggara, Timur Tengah, dan kalangan akademik Barat. Analisis evolusi tematik menunjukkan pergeseran dari fokus awal pada produksi konten dan etika media, menuju isu-isu mutakhir seperti visibilitas algoritmik, literasi digital, dan efektivitas da'wah di ruang virtual. Penelitian ini memberikan kontribusi terhadap pemahaman yang lebih dalam tentang perkembangan da'wah Digital sebagai bidang kajian akademik serta menawarkan wawasan bagi akademisi, praktisi, dan pembuat kebijakan dalam studi komunikasi dan media Islam.